The alterations of airway and intestine microbiota in asthma: a systematic review and meta-analysis - Li, Wenpei; Lu, Kezhen; Tang, Jisen; Chen, Yanyu; Lu, Yifan; Hu, Xiaoyan; Zhu, Haixing; Feng, Yun (Frontiers in Immunology, 2025)
BackgroundEmerging evidence highlights notable differences in microbial ecology between individuals with asthma and healthy controls (HC). This meta-analysis aims to compile data on microbial diversity indices in the airway and intestinal microbiota of both groups for comparative analysis.MethodsWe conducted a thorough systematic search of literature in PubMed, Embase, the Web of Science, and the Cochrane Library to find English-language studies focused on airway and intestinal microbiota in asthma, published from May 16, 2020 to May 16, 2025. We extracted data regarding microbial diversity indices to facilitate comparisons between the asthma group and HC.Results26 studies were included in this systematic review. Our analysis revealed no significant differences in alpha diversity between the two participant groups; however, beta diversity exhibited significant differences in 9 of the studies reviewed.ConclusionOur meta-analysis did not confirm the hypothesis that asthma shows lower alpha diversity than HC. To enhance understanding and inform future diagnostic and therapeutic approaches, further studies should be conducted with larger sample sizes and more robust methodologies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251113790.